Welding - Modern Topics 2021
DOI: 10.5772/intechopen.92301
|View full text |Cite
|
Sign up to set email alerts
|

Heat Treatment of Metastable Beta Titanium Alloys

Abstract: Heat treatment of metastable beta titanium alloys involves essentially two steps-solution treatment in beta or alpha+beta phase field and aging at appropriate lower temperatures. High strength in beta titanium alloys can be developed via solution treatment followed by aging by precipitating fine alpha (α) particles in a beta (β) matrix. Volume fraction and morphology of α determine the strength whereas ductility is dependent on the β grain size. Solution treatment in (α + β) range can give rise to a better com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 68 publications
(94 reference statements)
0
11
0
Order By: Relevance
“…In contrast to the influence of α" precipitation, the possible formation of the athermal ω phase during ST is correlated with a rise in strength, reduced ductility, and, in most cases, an unsatisfactory increase in elastic modulus [42]. However, knowing that the addition of about 5-7 wt.% of Zr to Ti-Nb/Mo-Fe alloys represents a sufficient quantity to suppress the formation of athermal ω precipitates during ST (water quenching) [47], it can be concluded that the Zr content (7.6 wt.%) from the present case, alongside other alloying elements, would be sufficient to ensure this desideratum.…”
Section: Micro-structural Analysis Of the Studied Alloymentioning
confidence: 88%
See 4 more Smart Citations
“…In contrast to the influence of α" precipitation, the possible formation of the athermal ω phase during ST is correlated with a rise in strength, reduced ductility, and, in most cases, an unsatisfactory increase in elastic modulus [42]. However, knowing that the addition of about 5-7 wt.% of Zr to Ti-Nb/Mo-Fe alloys represents a sufficient quantity to suppress the formation of athermal ω precipitates during ST (water quenching) [47], it can be concluded that the Zr content (7.6 wt.%) from the present case, alongside other alloying elements, would be sufficient to ensure this desideratum.…”
Section: Micro-structural Analysis Of the Studied Alloymentioning
confidence: 88%
“…The β-transus temperature (T β ) represents an important parameter for selecting the heat treatment temperatures. The T β value strongly depends on the alloying elements: α-stabilizers increase T β , β-stabilizers decrease T β , while the neutral elements do not change T β [42]. Equation (1) to find the T β value is given below [32]:…”
Section: The Reason For Selecting the Thermomechanical Processing Parametersmentioning
confidence: 99%
See 3 more Smart Citations